Restorative Justice Efforts Inin The Settlement Ofof Narcotic Crime Byby Children (No. 10/Pid.Sus-Anak/2018/PN.K) - Riski Khoiria Hutagalung; Efendilius Halawa; Winta Hayati (LEGAL BRIEF, 2023)
Protection Commission (KPAI) has created an increase in the involvement of children in black drug trafficking. Meanwhile, in 2017, in a survey conducted by the Ministry of Health, it was stated that there were more than 22,000 drug problems in high school students' areas, 6,000 cases in junior high school students, and 3,000 problems for elementary school students. With the aim of this research, it is hoped that law enforcement officials, especially the police, must become the initiator and facilitator of the prosecution of children in conflict with the law by appealing to all parties involving perpetrators, victims, their parents, the surrounding community, or the school to sit together in dialogue meetings. the settlement process uses a restorative justice approach. This study uses a statutory approach (statute approach) and a case approach (case approach). Apart from the debate about the issue of violations of the Narcotics Law which are increasingly becoming a frightening crime for the community, child actors should be given their rights to obtain recovery as aspired to in the principle of restorative justice. However, in reality, in Verdict No. 10/Pid. Sus-Children/ 2018/ PN. Then, the child actually experienced significant difficulties in recovering mentally and psychologically because the panel of judges sentenced him to one year and 6 months in prison. Based on the above review, it can be concluded that the panel of judges in Verdict Number 10/Pid. Sus-Children/ 2018/ PN. KDI has not really thought deeply about implementing the principles of benefit and restorative justice. These considerations should be a serious concern for each judge when dealing with children as defendants in any matter. This journal examines the Medan City District Court decision No. 10/Pid.Sus-Anak/2018/PN.K in the case of criminal acts of Narcotics, Narcotics Law No. 35 of 2009 concerning Narcotics, in which the perpetrators of the crime of narcotics abuse who are subject to criminal sanctions are clearly categorized as minors. However, in their decision, the panel of judges imposed a prison sentence of one year and six months, while in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This paper focuses on examining the extent to which judges consider the principles of expediency and restorative justice for the child in Decision Number 10/Pid.Sus-Anak/2018/PN.Kdi. The research in this writing is normative juridical law research with a case study approach. The conclusion is that judges are more likely to focus their considerations on the side of legal certainty without being more observant in exploring restorative justice from the decisions they pass on child defendants.